A deletion mutation within the ATBF1 gene is strongly associated with goat litter size. Issue 2 (3rd March 2020) - Wang, Ke; Hui, Yiqing; Zhang, Shaoli; Wang, Ming; Yan, Hailong; Zhu, Haijing; Qu, Lei; Lan, Xianyong; Pan, Chuanying
Abstract: AT motif-binding factor ( ATBF1 ) is a transcription factor that suppresses carcinogenesis and induces neuronal differentiation, as well as it directly interacts with estrogen receptor (ER) and regulates progesterone receptors signaling. Thus ATBF1 gene will possibly greatly affect reproductive tratis in animals. According to our available findings, two indel (insertion/deletion) variants (12-bp indel; 6-bp indel) within the ATBF1 gene were found in Shaanbei White cashmere goats (SWCG). The objective of this work was to investigate their association with litter size in Shaanbei White Cashmere goat. The association analyses uncovered that ATBF1 -12bp indel was strongly related to the first-birth litter size in SWCG population ( n  = 1195, P  = 1.0 × 10 −3 ). Individuals with DD genotype ( n  = 445) had the best litter size when compared with those of ID genotype ( n  = 420) and DD genotype ( n  = 330). Besides, Chi-square tests of different litter size individuals showed that multi-kids individuals had higher "D" allelic frequencies and "DD" genotypic frequencies ( p  < 0.01). These findings suggested the ATBF1 -12bp deletion mutation was significantly associated with reproduction-related trait, suggesting that this deletion could be used as an effective molecular marker for litter size in goat breeding.